Effect of Feeding Pomegranate and Rohitaka on Rumen Fermentation Parameters in Male Buffalo Calves - Singh, Iqbal; Hundal, Jaspal Singh; Singh, Gurpreet; Wadhwa, Manju; Lamba, Jaspal Singh (Indian Journal of Animal Nutrition, 2018)
To study the effect of herb supplementation, 6 fistulated animals were selected and divided randomly into 2 groups of 3 each. All the animals were offered conventional diet with roughage to concentrate ratio of 65:35 on DM basis as TMR with or without Pomegranate (Anar chal) or Rohitaka @ 2% of DMI. After 15 days adaptation period, rumen liquor was collected at 0, 2, 4, 6, 8, 12hr post feeding for three days, pooled and analyzed for various parameters.The study revealed that Anar chal had significantly higher (p